46O Impact of early introduction of steroid on immune-checkpoint inhibitors (ICI) in patients with advanced non-small cell lung cancer treated. (15th December 2019) - De Giglio, A; Mezquita, L; Auclin, E; Blanc-Durand, F; El-Amarti, L; Caramella, C; Bernal, G Martinez; Hendriks, L; Ferrara, R; Naltet, C; Lavaud, P; Gazzah, A; et al.
Abstract: Background: The use of steroids at baseline before ICI initiation has been associated with poor outcomes, particularly when their indication is related to cancer symptoms. It is poorly known if the initiation of steroids during the course of ICI impacts the outcomes. Methods: Retrospective analysis of advanced NSCLC patients treated with ICI at Institute Gustave Roussy. Eligible: steroids-naïve at baseline, initiating steroids therapy (≥10 mg of prednisone-equivalent) within the first 8 weeks of ICI. We correlated steroid use with outcomes, including progression-free survival (PFS) and overall survival (OS). Results: In an overall population of 424 patients treated with ICI, 250 were steroids-naïve at baseline. The median age was 63 years (range 30–92), most of them were male (65.5%), current or former smoker (90.6%), with non-squamous histology (76.1%) and ECOG PS 0/1 (76.8%). A total of 49 patients received early steroids: 39 patients for cancer-related indications [dyspnea (50%), brain metastasis (15.8%), pain (7.9%), superior vena cava syndrome (7.9%), fatigue (5.3%) and others (13.1%)]. For the 10 others indications were: immune-related adverse events (54.6%), COPD exacerbation (27.1%) and others (18.2%). Median (m) PFS and OS were 1.9 months (mo.) [95% CI, (1.77-2.40)] and 10 mo. [95% CI, (8.11-12.91)], respectively. Early introduction of steroids under ICI was associated with a shorter median (m) PFS (1.3 mo., P < 0.0001), and mOS (2.3 mo., P < 0.0001). Patients receiving steroids for cancer-related symptoms had significantly poorer outcomes with mPFS of 1.1 mo. [95% CI, 0.85-1.51] and mOS of 1.9 mo. [95% CI, (1.54-2.4)]. No differences were observed between the group of patients that started steroids for other indications [mPFS 2.7 mo. (1.21-NR); mOS 13.4 mo., (4.30-NR)] and the group without steroids [mPFS 2.6 mo. (2.20-3.94); mOS 13.8 mo. (11.4-18)]. Early steroids introduction for cancer-related symptoms was an independent prognostic factor for both poor PFS [HR 3.04; 95% CI, (1.38-6.66); P = 0.006] and OS [HR 1.21; 95%CI, (0.53-2.8); P < 0.0001]. Conclusion: Introduction of steroids within the first 8 weeks of ICI has no detrimental impact on prognosis if the indication is not related to cancer symptoms. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: L. Mezquita: Advisory / Consultancy: Roche Diagnostics; Speaker Bureau / Expert testimony: Bristol-Myers; Speaker Bureau / Expert testimony: Squibb; Speaker Bureau / Expert testimony: Tecnofarma; Speaker Bureau / Expert testimony: Roche; Speaker Bureau / Expert testimony: AstraZeneca; Travel / Accommodation / Expenses: Bristol-Myers; Travel / Accommodation / Expenses: Squibb; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Chugai; Research grant / Funding (institution), Mentorship Program: AstraZeneca. E. Auclin: Travel / Accommodation / Expenses: Mundipharma. C. Caramella: Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: MSD; Advisory / Consultancy: Roche; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Amgen. L. Hendriks: Research grant / Funding (institution): Roche; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Bristol-Myers Squibb; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Bristol-Myers Squibb; Non-remunerated activity/ies, Mentorship Program: AstraZeneca; Non-remunerated activity/ies, Webinars: Quadia. R. Ferrara: Advisory / Consultancy: MSD; Travel / Accommodation / Expenses: Pfizer. P. Lavaud: Travel / Accommodation / Expenses: Astellas-Pharma; Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Ipsen; Travel / Accommodation / Expenses: Janssen Oncology; Travel / Accommodation / Expenses: Mundi Pharma. A. Gazzah: Research grant / Funding (institution), Travel / Accommodation / Expenses: Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Research grant / Funding (institution): Aduro Biotech; Research grant / Funding (institution): Agios Pharmaceuticals; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): Argen-X Bvba; Research grant / Funding (institution): Arno Therapeutics; Research grant / Funding (institution): Astex Pharmaceuticals; Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Aveo; Research grant / Funding (institution): Bayer Healthcare Ag; Research grant / Funding (institution): Bbb Technologies Bv; Research grant / Funding (institution): Beigene; Research grant / Funding (institution): Bioalliance Pharma; Research grant / Funding (institution): Biontech Ag; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution): Bristol Myers Squibb; Research grant / Funding (institution): Celgene Corporation; Research grant / Funding (institution): Chugai Pharmaceutical Co.; Research grant / Funding (institution): Clovis Oncology, Daiichi Sankyo, Debiopharm S.A., Eisai, Exelixis, Forma, Gamamabs, Genentech, Inc., Gilead Sciences, Inc, Glaxosmithkline, Glenmark Pharmaceuticals, H3 Biomedicine, Inc, Hoffmann La Roche Ag, Incyte Corporation, Innate Pharma, Iris Servie; Research grant / Funding (self): Janssen Cilag; Non-remunerated activity/ies, Drug Supplied: AstraZeneca, Bayer, Bristol-Myers Squibb, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche. J. Adam: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Bayer; Honoraria (self): MSD; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Takeda; Honoraria (self): Chugai. D. Planchard: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Celgene; Advisory / Consultancy, Research grant / Funding (institution): Daiichi Sankyo; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Merck; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: prIME Oncology; Advisory / Consultancy: Peer CME; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Research grant / Funding (institution): Medimmun; Research grant / Funding (institution): Sanofi-Aventis; Research grant / Funding (institution): Taiho Pharma; Research grant / Funding (institution): Novocure. N. Chaput: Research grant / Funding (institution): Cytune Pharma, GSK, Sanofi; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Speaker Bureau / Expert testimony: Sanofi. B. Besse: Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Amgen; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Biogen; Research grant / Funding (institution): Blueprint Medicines; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Celgene; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Ignyta; Research grant / Funding (institution): IPSEN; Research grant / Funding (institution): Merck KGaA; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Nektar; Research grant / Funding (institution): Onxeo; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Pharma Mar; Research grant / Funding (institution): Sanofi; Research grant / Funding (institution): Spectrum Pharmaceuticals; Research grant / Funding (institution): Takeda; Research grant / Funding (institution): Tiziana Pharma. All other authors have declared no conflicts of interest.